On the type series of Scinax perpusillus (Lutz & Lutz, 1939) (Anura: Hylidae) - Colaço, Gustavo; Silva, Helio Ricardo Da (Zootaxa, 2016)
The literature regarding the type series of Scinax perpusillus (Lutz & Lutz, 1939) presents two distinct numbers for the holotype. In 1973, thirty-four years after the description, Bertha Lutz associated numbers to the type series. This numbering has been followed by subsequent reviewers of Scinax ever since, with exception of Peixoto (1987) who assigned another number to the holotype. Our reevaluation of the literature and examination of the type series allowed us to access that, in both cases, the numbers were incorrectly assigned to the specimens and determine the proper museum numbers for this series.